Tip1/CLIP-170 protein is required for correct chromosome poleward movement in fission yeast. - Sherilyn Goldstone (Public Library of Science (PLoS), 2010)
The plus-end microtubule binding proteins (+TIPs) play an important role in the regulation of microtubule stability and cell polarity during interphase. In S. pombe, the CLIP-170 like protein Tip1, together with the kinesin Tea2, moves along the microtubules towards their plus ends. Tip1 also requires the EB1 homolog Mal3 to localize to the microtubule tips. Given the requirement for Tip1 for microtubule stability, we have investigated its role during spindle morphogenesis and chromosome movement. Loss of Tip1 affects metaphase plate formation and leads to the activation of the spindle assembly checkpoint. In the absence of Tip1 we also observed the appearance of lagging chromosomes, which do not influence the normal rate of spindle elongation. Our results suggest that S. pombe Tip1/CLIP170 is directly or indirectly required for correct chromosome poleward movement independently of Mal3/EB1.